(untitled) (Orfeu, 2023)
This work presents a study on musical creation made in studios through technological use, focusing on practices applied to popular music and the use of the computer as a creative tool. Thus, the objective is to understand the main sound creation and manipulation techniques used in this context, in order to apply them in experimental creation processes. Therefore, a historical overview of the main technological changes of the 20th and early 21st centuries that impacted the compositional thinking of the period is presented, in addition to the descriptive analysis of the creation of the album "When We All Fall Asleep, Where Do We Go?" by singer Billie Eilish, addressing aspects of musical creation in the home studio. Testimonials and interviews of composers were used as a methodological resource for analysis, besides literature reviews. Finally, the compositional report of the cello piece entitled "UCO" is presented, conceived by the authors through the analyzes carried out.